Fe-polypyrrole/reduced graphene oxide composites for Li-O2 batteries - Lim, Bryan Qi Ming (2014)
The Lithium-Oxygen (Li-O2 or Li-air) batteries have garnered worldwide interest due to its high theoretical values attainable. If successfully developed, it is projected to provide a key role in the electrification of transport. However, due to the high over-potential of the battery, it is still a challenge to use it. Hence, the author proposes the use of Fe-polypyrrole/reduced graphene oxide composites as O2 electrodes for the Li-O2 batteries. The author provides evidence that the use of the reduced graphene oxide results in products that exhibits high round-trip efficiencies and stable cycling performances. The author also discusses his view on the challenges and promises facing the development of the Li-O2 batteries as well as the choices of materials and the current understanding of their chemistry.